Heparin mimetics: Their therapeutic potential - Mohamed, Shifaza; Coombe, Deidre (Multidisciplinary Digital Publishing Institute (MDPI) AG, 2017)
Â© 2017 by the authors. Licensee MDPI, Basel, Switzerland. Heparin mimetics are synthetic and semi-synthetic compounds that are highly sulfated, structurally distinct analogues of glycosaminoglycans. These mimetics are often rationally designed to increase potency and binding selectivity towards specific proteins involved in disease manifestations. Some of the major therapeutic arenas towards which heparin mimetics are targeted include: coagulation and thrombosis, cancers, and inflammatory diseases. Although Fondaparinux, a rationally designed heparin mimetic, is now approved for prophylaxis and treatment of venous thromboembolism, the search for novel anticoagulant heparin mimetics with increased affinity and fewer side effects remains a subject of research. However, increasingly, research is focusing on the non-anticoagulant activities of these molecules. Heparin mimetics have potential as anti-cancer agents due to their ability to: (1) inhibit heparanase, an endoglycosidase which facilitates the spread of tumor cells; and (2) inhibit angiogenesis by binding to growth factors. The heparin mimetic, PI- 88 is in clinical trials for post-surgical hepatocellular carcinoma and advanced melanoma. The antiinflammatory properties of heparin mimetics have primarily been attributed to their ability to interact with: complement system proteins, selectins and chemokines; each of which function differently to facilitate inflammation. The efficacy of low/non-anticoagulant heparin mimetics in animal models of different inflammatory diseases has been demonstrated. These findings, plus clinical data that indicates heparin has anti-inflammatory activity, will raise the momentum for developing heparin mimetics as a new class of therapeutic agent for inflammatory diseases.